Timing of human preimplantation embryonic development is confounded by embryo origin - Kirkegaard, K. (Hum Reprod, 2016)
STUDY QUESTION: To what extent do patient- and treatment-related factors explain the variation in morphokinetic parameters proposed as embryo viability markers? SUMMARY ANSWER: Up to 31% of the observed variation in timing of embryo development can be explained by embryo origin, but no single factor elicits a systematic influence. WHAT IS KNOWN ALREADY: Several studies report that culture conditions, patient characteristics and treatment influence timing of embryo development, which have promoted the perception that each clinic must develop individual models. Most of the studies have, however, treated embryos from one patient as independent observations, and only very few studies that evaluate the influence from patient- and treatment-related factors on timing of development or time-lapse parameters as predictors of viability have controlled for confounding, which implies a high risk of overestimating the statistical significance of potential correlations. STUDY DESIGN, SIZE, DURATION: Infertile patients were prospectively recruited to a cohort study at a hospital fertility clinic from February 2011 to May 2013. Patients aged <38 years without endometriosis were eligible if ≥8 oocytes were retrieved. Patients were included only once. All embryos were monitored for 6 days in a time-lapse incubator. PARTICIPANTS/MATERIALS, SETTING, METHODS: A total of 1507 embryos from 243 patients were included. The influence of fertilization method, BMI, maternal age, FSH dose and number of previous cycles on timing of t2-t5, duration of the 2- and 3-cell stage, and development of a blastocoel (tEB) and full blastocoel (tFB) was tested in multivariate, multilevel linear regression analysis. Predictive parameters for live birth were tested in a logistic regression analysis for 223 single transferred blastocysts, where time-lapse parameters were investigated along with patient and embryo characteristics. MAIN RESULTS AND THE ROLE OF CHANCE: Moderate intra-class correlation coefficients (0.16–0.31) were observed for all parameters except duration of the 3-cell stage, which demonstrates that embryos from one patient elicit clustering at a patient level. No single patient- and treatment-related factor was found to systematically influence the timing from cleavage to blastocyst stage, which indicates that no individual patient-related factor can be identified that separately explains the clustering throughout the entire developmental stages. The blastocyst parameters were more affected by patient-related factors than cleavage stage parameters, as tEB occurred significantly later with older age (0.29 h/year (95% confidence interval: CI 0.03; 0.56)), while both tEB and tFB occurred significantly later with increasing dose of FSH (tEB: 0.12 h/100 IU FSH (95% CI 0.01;0.24); tFB 0.14 h/100 IU FSH (95% CI 0.03;0.27)) and with more previous attempts (tEB: 1.2 h/attempt (95% CI 0.01;2.5); tFB 1.4 h/attempt (0.10;2.7)). Fertilization method affected timing of the first division, with ICSI embryos cleaving significantly faster than IVF embryos (−3.6% (95% CI −6.4; −0.77)), whereas no difference was found in the subsequent divisions. The univariable regression analysis identified female age, cumulative FSH dose, degree of blastocyst expansion, score of the inner cell mass and timing of full blastocyst formation as predictors of live birth. The timing of full blastocyst formation (tFB) did not remain significant when adjusting for age, number of previous cycles and cumulative FSH dose, which were the parameters shown to influence tFB in the mixed regression model. LIMITATIONS, REASONS FOR CAUTION: Only good prognosis patients were enrolled, so these results may not be generalized to all infertile women. Not all patient-related factors were investigated. WIDER IMPLICATIONS OF THE FINDINGS: Our findings underline the importance of treating embryos as dependent observations and suggest a high risk of patient-based confounding in retrospective studies. The impact of confounders and the embryo origin needs to be addressed in order to apply appropriate statistical models in observational studies. Furthermore, this observation emphasizes the need for RCTs for evaluating use of time-lapse parameters for embryo selection. STUDY FUNDING/COMPETING INTERESTS: Funding for the cohort study was provided by the Lippert Foundation, the Toyota Foundation, the Aase og Einar Danielsen foundation and NordicInfu Care research grant. Research at the Fertility Clinic, Aarhus University Hospital is supported by an unrestricted grant from MSD and Ferring. K.K. is funded by a grant from the Danish Council for Independent Research Medical Sciences. The authors declare no competing interest.